The complete mitochondrial DNA genome of a cone snail, Conus betulinus (Neogastropoda: Conidae), from the South China sea - Yanling Liao; Jinxing Fu; Bingmiao Gao; Tianle Tang (Mitochondrial DNA. Part B. Resources, 2021)
The complete mitochondrial genome of the tubular cone snail Conus betulinus is presented in this study. The C. betulinus mitochondrial genome was 16,240 bp with 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, 2 ribosomal RNA (rRNA) genes, and a non-coding AT-rich region (D-loop). The overall base composition was estimated to be 25.67% for A, 38.26% for T, 21.38% for G, and 14.69% for C, with a high A + T content of 63.93%. Phylogenetic analyses based on 13 PCGs showed the close relationship of vermivorous C. betulinus with the common ancestor of molluscivorous Conus textile and Conus gloriamaris, providing a basis for further studies on the phylogenetics of cone snails according to their dietary type.